Kiribati : 2001 Article IV. (IMF Staff Country Reports; Country Report ;, 2001)
Kiribati's economic policies reflect the country's communally oriented values that favor social cohesion over individual self-reliance and the rough and tumble of the market economy. Unfavorable external conditions, fiscal slippages, and the lack of structural reforms have led to a weakening in Kiribati's external and fiscal positions. To achieve sustainable medium-term growth, timely implementation of fiscal consolidation and structural reforms is critical. Public enterprise reform and privatization, along with civil service rationalization, should be at the top of the reform agenda.